Congruencies in Increased Mortality Rates, Years of Potential Life Lost, and Causes of Death Among Public Mental Health Clients in Eight States - Craig W. Colton, PhD; Ronald W. Manderscheid, PhD (Centers for Disease Control and Prevention, 2006)
Introduction Mortality rates are used as global measures of a population's health status and as indicators for public health efforts and medical treatments. Elevated mortality rates among individuals with mental illness have been reported in various studies, but very little focus has been placed on interstate comparisons and congruency of mortality and causes of death among public mental health clients. Methods Using age-adjusted death rates, standardized mortality ratios, and years of potential life lost, we compared the mortality of public mental health clients in eight states with the mortality of their state general populations. The data used in our study were submitted by public mental health agencies in eight states (Arizona, Missouri, Oklahoma, Rhode Island, Texas, Utah, Vermont, and Virginia) for 1997 through 2000 during the Sixteen-State Study on Mental Health Performance Measures, a multistate study federally funded by the Center for Mental Health Services in collaboration with the National Association of State Mental Health Program Directors. Results In all eight states, we found that public mental health clients had a higher relative risk of death than the general populations of their states. Deceased public mental health clients had died at much younger ages and lost decades of potential life when compared with their living cohorts nationwide. Clients with major mental illness diagnoses died at younger ages and lost more years of life than people with non-major mental illness diagnoses. Most mental health clients died of natural causes similar to the leading causes of death found nationwide, including heart disease, cancer, and cerebrovascular, respiratory, and lung diseases. Conclusion Mental health and physical health are intertwined; both types of care should be provided and linked together within health care delivery systems. Research to track mortality and primary care should be increased to provide information for additional action, treatment modification, diagnosis-specific risk, and evidence-based practices.